Conservation genetics of the rare Iberian endemic Cheirolophus uliginosus (Asteraceae). (14th July 2015) - Vitales, Daniel; García‐Fernández, Alfredo; Garnatje, Teresa; Vallès, Joan; Cowan, Robyn S.; Fay, Michael F.; Pellicer, Jaume
<x xml:space="preserve">Abstract</x> Cheirolophus uliginosus is a rare species, endemic to the south‐western Iberian Peninsula, and listed as a characteristic taxon from the temperate Atlantic wet heaths, a priority habitat for conservation by the European Union. The conservation status of this species in most of its distribution area is poorly known, but, in recent times, some populations have disappeared and there has been a reduction in the number of individuals in others. In this context, we analysed the effects of population size on genetic diversity, revealing that genetic erosion and inbreeding depression could be having a significant impact on smaller populations. Furthermore, we studied the patterns of genetic structure and variability at the species level, finding a strikingly low within‐population diversity and high among‐population genetic differentiation. Finally, the genetic structure analyses suggested a long and complex phylogeographical history of C. uliginosus in the region, in agreement with the climate relict status proposed for this species. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 179, 157–171.